PENGARUH DISPOSISI MATEMATIS DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 2 TANAH GROGOT - Isnaini Saleh, Andi; Rusdiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning activities are understood as a phenomenon experienced by students, which is seen in behavioral growth due to interactions with the surrounding environment, which is inseparable from the influence of mathematical disposition and learning environment. The purpose of this study was to determine whether there is an influence of mathematical disposition ( ) and learning environment ( ) on mathematics learning outcomes ( ) of grade VII students at SMP Negeri 2 Tanah Grogot. The method applied in this research is a quantitative approach through an ex post facto design framework. The population in this research includes all grade VII students at SMP Negeri 2 Tanah Grogot in the 2024/2025 academic year with a totaling 198 students. The sample was selected through a probability sampling method with a total sample of 155 students. The research instruments include questionnaires and tests. The data obtained were analyzed using descriptive statistics and inferential, namely through multiple linear regression analysis at a significance level ( ) of 5%. Descriptive findings show that the average mathematical disposition and learning environment are in the moderate category, and the average mathematics learning outcomes with a value of 59,05 are in the poor category. The results of the inferential analysis using multiple linear regression method, obtained a regression equation model: . The resulting coefficient of determination ( ) is 0,332. The results of the inferential analysis for the t test show a significance value for the regression coefficient (mathematical disposition) and the regression coefficient value (learning environment) less than , namely and , then is rejected, meaning that the mathematical disposition variable influences students’ mathematics learning outcomes and the learning environment variable also influences students’ mathematics learning outcomes. So, it can be concluded that there is an influence of mathematical disposition and learning environment on the mathematics learning outcomes of grade VII students at SMP Negeri 2 Tanah Grogot.